Rancang Bangun Sistem Informasi Administrasi Akademik Berbasis Web Dengan Menggunakan xHTML (Studi Kasus Pada SMAN 8 Surabaya) - Hansyi, Awad Achmad; Lusiani, Titik; Sutanto, Teguh (Jurnal JSIKA, 2012)
Academic administration student information system is a web based system that can provide periodic reports students´ online activity, whether it be information on grades, attendance, finances, and scores of students who are concerned violations. Along with the increased number of students from year to year, SMAN 8 has disadvantages in terms of student academic information delivery activities to parents. One solution of the problem is the construction of an information system with a web-based academic administration using xHTML for students who can be accessed through mobile devices. This system was built based on web using HTML programming language, xHTML, PHP and Javascript and uses MySQL database. This application can assist the academic functions in terms of student data storage to deliver information on academic activities for students and parents or guardians. This system was built as a means of improving the quality of education in schools as well as easy solutions for the SMAN 8. This system can perform maintenance and management of process data into information useful in disseminating information on student academic activities to parents .Keywords : SMAN 8, Academic Information System, PHP, xHTML.